Tissue Culture of Oil Palm: Finding the Balance Between Mass Propagation and Somaclonal Variation - Weckx, Sylvie; Inzé, Dirk; Maene, Ludo (Frontiers in Plant Science, 2019)
The oil palm (Elaeis guineensis Jacq.) is typically propagated in vitro by indirect somatic embryogenesis, a process in which somatic cells of an explant of choice are, via an intermediate phase of callus growth, induced to differentiate into somatic embryos. The architecture of the oil palm, lacking axillary shoots, does not allow for vegetative propagation. Therefore, somatic embryogenesis is the only alternative to seed propagation, which is hampered by long germination times and low germination rates, for the production of planting material. The current oil palm somatic embryogenesis procedure is associated with several difficulties, which are described in this review. The limited availability of explants, combined with low somatic embryo initiation and regeneration rates, necessitate the proliferation of embryogenic structures, increasing the risk for somaclonal variants such as the mantled phenotype. Several ways to improve the efficiency of the tissue culture method and to reduce the risk of somaclonal variation are described. These include the use of alternative explants and propagation techniques, the introduction of specific embryo maturation treatments and the detection of the mantled abnormality in an early stage. These methods have not yet been fully explored and provide interesting research field for the future. The development of an efficient oil palm micropropagation protocol is needed to keep up with the increasing demand for palm oil in a sustainable way. Mass production of selected, high-yielding palms by tissue culture could raise yields on existing plantations, reducing the need for further expansion of the cultivated area, which is often associated with negative environmental impacts.